Modern geothermal HVAC engineering and control applications - Egg, Jay; Cunniff, Greg; Orio, Carl D. (McGraw-Hill Education, 2013)
"With a focus on market needs and customer goals, this practical guide explains how to realize the full potential of geothermal HVAC by integrating hydronic systems and controls at maximum capacity. This book explains how to engineer and specify geothermal HVAC for building projects in varying geographic regions. Typical details on control parameters are provided. By using the proven methods in this innovative resource, you will be able to develop highly efficient, long-lasting, and aesthetically pleasing geothermal HVAC systems. "--Back cover.